Optimizing Packing And Logistics Costs: A KPI Study In Cement Industry (Journal of Informatics Education and Research, 2025)
The cement industry faces significant challenges in managing packing and logistics costs, which constitute a substantial portion of overall operational expenses. This study examines the optimization of packing and logistics costs through the systematic application of Key Performance Indicators (KPIs) in cement manufacturing and distribution operations. A comprehensive analysis of supply chain operations, distribution network optimization, and cost components was conducted using data from multiple cement industry case studies. The research identifies critical KPIs including total logistics costs, on-time delivery performance, distribution efficiency, inventory management metrics, and packaging optimization indicators. Findings reveal that total logistics costs in cement projects range from 14.60% to 22.56% of total investment costs, with foreign logistics costs and customs clearance representing the largest components at 6.62% and 6.52% respectively. The study demonstrates that implementation of Mixed Integer Linear Programming (MILP) optimization models can reduce supply chain costs by 4-7%, with distribution process efficiency improvements reaching up to 44%. The research establishes a framework for cement industry practitioners to implement strategic KPI-based monitoring systems that enhance cost efficiency, improve delivery performance, and optimize resource utilization across the packing and logistics value chain. This study contributes to the body of knowledge by providing empirical evidence of logistics cost optimization opportunities and establishing benchmarking standards for the cement industry.